Blood Pressure Control at Rest and during Exercise in Obese Children and Adults - Konstantina Dipla; George P. Nassis; Ioannis S. Vrabas (Journal of Obesity)
The hemodynamic responses to exercise have been studied to a great extent over the past decades, and an exaggerated blood pressure response during an acute exercise bout has been considered as an indicator of cardiovascular risk. Obesity is a major factor influencing the blood pressure response to exercise since evidence indicates that the arterial pressure response to exercise is exacerbated in obese compared with lean adults. Signs of augmented responses (such as an exaggerated blood pressure response) to physical exertion appear early in life (from the prepubertal years) in obese individuals. Understanding the mechanisms that drive the altered hemodynamic responses during exercise in obese individuals and prevent the progression to hypertension is vitally important. This paper focuses on the evidence linking obesity with alterations of the autonomic nervous system and discusses the potential mechanisms and consequences of the altered sympathetic nervous system behavior in obese individuals at rest and during exercise. Furthermore, this paper presents the alterations in the reflex regulatory mechanisms (“exercise pressor reflex” and baroreflex) in obese children and adults and addresses the effects of training on obesity-related disturbances.